AN OVERVIEW OF RECENT SCENARIO OF CORPORATE GOVERNANCE IN HEALTH CARE INDUSTRY AS A SUSTAINABILITY STRATEGY (International Journal of Food and Nutritional Sciences, 2022)
This examine is ambitious to discover the exclusive forms of company governance in the fitness area, how they act together, and examine the evolving studies trend via a scientific literature assessment (SLR) in the length 2015-2019. The Scopus and ISI internet of technological know-how databases were used to choose the 167 articles analyzed. The ensurance of corporate governance research changed into focused on adapting the PRISMA evaluation, emphasizing the environment which corporate governance belongs to and evaluation of the co-occurrence of the key phrases used in the studies. Via Grounded principle, a conceptual model become advanced, emphasizing the main characteristics that impact governance on the macro-, meso- and micro-stages, in the health region, and raising a future time table for future studies on this location: (1) exceptional of health care, (2) corporate social responsibility in health, (3) health threat control and 4. international health governance. The consequences of this research intention to manual governments in the direction of developing regulatory developments, warning about the dangers of the impact of company governance on health, or the lack of it, on the first-class of offerings. Evaluation of the pleasant of health care is essentially related to the environment, despite the fact that this thing has obtained little consideration from researchers.